Unveiling difficulties in performing prayer movements among adults with disabling vestibular disorders - Mohd Sakeri, Nurul Syarida; Zakaria, Mohd Normani; Abdul Wahat, Nor Haniza; Zainun, Zuraida; Salim, Rosdan; Jamaluddin, Saiful Adli (2019)
It is evident that vestibular disordered patients have difficulties in performing their daily life activities. The aim of the present study was to unveil the specific body movements and positions that would trigger or worsen dizziness and/or vertigo among adults when performing their daily prayers. In this cross-sectional study, Malay Muslim patients (n = 83) who had been clinically diagnosed with vestibular disorders were recruited. All fulfilled the inclusion criteria and were phone-interviewed using a validated checklist. Of 83 respondents, 41% (n = 34) reported that they had notable difficulties in performing their daily prayers. Of this, 44% of the respondents could not stand still during the prayer, in which 12% needed to be seated to fulfil the obligations. Next to standing, the second most prominent problem that the respondents reported was prostration (38%), followed by bowing (21%). A small percentage of the respondents (3%) reported difficulties in turning the head to the left and right (i.e., the final gesture in the prayer). To conclude, a high percentage of vestibular disordered patients had difficulties in performing their regular prayers as the specific body positions and movements would trigger or worsen their dizziness and/or vertigo. Consequently, Muslims with disabling vestibular disorders would not be able to fulfil their obligatory prayers, which can be disappointing. The present study findings can serve as the reference for future big scale research, as well as for developing an effective vestibular rehabilitation technique.